Productive performance of grasslands with different combinations of orchard grass (Dactylis glomerata L.), perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) - Rojas García, Adelaido Rafael; Hernández Garay, Alfonso; Ayala, Walter; Mendoza Pedroza, Sergio Iban; Cancino, Santiago Joaquín; Vaquera Huerata, Humberto; Santiago Ortega, Mario Alberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
In central Mexico there animal production systems whose major component using pure and associated grasslands. The objective of this research was to evaluate four associations, two grasses and legume planted in different proportions. Treatments consisted of the following associations: 20-40-40, 00-50-50, 40-20-40, and 50-00-50% of orchard grass (Ov), perennial ryegrass (Ba) and white clover (Tr) respectively. The treatments were randomly distributed in 12 experimental plots of 9 and 8 m, according to a design of a randomized complete block with three replications. Dry matter yield, growth rate, botanical and morphological composition and plant height were evaluated. In the association's annual yield higher performance were presented; 40-20-40 and 20-40-40 with 20.182 and 19.146 kg DM ha-1 respectively and the lowest 00-50-50 association with 15.896 kg DM ha-1. The Association; 40-20-40 is the highest annual growth rate presented with 56 kg DM ha-1 d-1. Regardless of the season, botanical and morphological composition associations; 20-40-40, 40-20-40 and 50-00-50 which was higher clew sheet presented with an average of 50 %, the winter season were the highest percentage of ryegrass sheet presented to the association 00-50-50 to 32%. Regardless of the association in the spring season it was where greater height was obtained with an average of 37 cm and the lowest was in winter with an average of 15 cm. In conclusion the association; 40-20-40 was better in annual yield growth rate and lower height and the association was 00-50-50.